Konsep Pendidikan Berdasarkan Keteladanan Kepada Nabi Muhammad ṣallallāh ʿalaih wasallam Perspektif Shaykh Muhammad bin Abdul Wahhāb - Ainul Haris (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2021)
This study examines the concept of education in the perspective of Muhammad Ibn 'Abd al-Wahhāb which is based on his exemplary to the Prophet Muhammad ṣallallāh ʿalaih wasallam. The da'wah of Ibn 'Abd al-Wahhāb raises the pros and cons among Muslims. The issue of education and exemplary is kind a fundamental things in Islam, because for a Muslim the Prophet Muhammad ṣallallāh ʿalaih wasallam is the first figure to be followed by his words, carried out his orders and decisions and his behavior imitated or emulated. This research answers how the concept of education according to Shaykh Muhammad bin Abdul Wahhāb which is taken from the figure of the Prophet Shallallahu 'alaihi wa Sallam. The type of research that the writer uses is library research which specifically examines a problem to obtain data in the writing of this study. Sources of data in this study were obtained from primary data and secondary data. The primary sources in this  writing are the original works or writings of Shaykh Muhammad bin Abdul Wahhāb. The secondary sources in this study are educational books, journals of morality aqidah in Islam that are relevant to the research discussion. The approach used in this research is historical-philosophical. The data obtained were then analyzed by content analysis (content analysis).This research resulted in understanding the concept of Shaykh Muhammad bin Abdul Wahhāb about education that is in accordance with the salaf manhaj, namely ittiba '(imitating) the Prophet and based on al-Qur'ān and Hadith. This study also explains that Shaykh Ibn 'Abd al-Wahhāb carries out and teaches the concept of education in accordance with the teachings of the Prophet ṣallallāh ʿalaih wasallam. The method of delivering da'wah, thoughts and examples of behavior of Shaykh Muhammad bin Abdul Wahhāb is based on exemplary education to the Prophet with all its purity without subtracting or any addition out from it, as well as staying away from all prohibitions in the form of bid'ah, khurafat and things that deviate from Islamic teachings.